ANALISIS PEMBELAJARAN PENDIDIKAN AGAMA KRISTEN BERBASIS NYANYIAN DAN MUSIK DI SMA NEGERI 10 LATUHALAT KOTA AMBON - Rudy Zelfianus (SEKOLAH TINGGI TEOLOGI INJILI SETIA SIAU, 2025)
Christian Religious Education (PAK) in Christian schools often relies on a cognitive approach that is less able to involve the emotional and spiritual dimensions of students, so that the strengthening of Christian values ​​is limited. This study aims to examine the effect of music-based learning on strengthening Christian values ​​in students at SMA Negeri 10 Latuhalat, Ambon City. With a qualitative approach, data were collected through interviews, observations, and documentation, and analyzed using thematic analysis. The results showed that music is effective in strengthening the understanding of the values ​​of love, forgiveness, and humility, as well as encouraging students' emotional and spiritual growth. In addition, music-based activities increase students' active participation, strengthen interpersonal relationships, and encourage changes in students' attitudes to be more caring, honest, and humble. The implications of these findings indicate the importance of a music-based approach in PAK learning to enrich affective learning models and support creative and spiritual education policies in Christian schools.